The Influence Of Corporate Branding And Brand Ambassador On Customer Trust At Bank Syariah Indonesia Branch Office Panorama, Bengkulu City - Zosen Wandi Rahman; Nurul Hak; Khozin Zaki (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
Customer trust serves as the primary foundation for the sustainability of the Islamic banking industry. Following the merger of Bank Syariah Indonesia (BSI), the strengthening of corporate brand identity and the utilization of brand ambassadors were implemented as strategic approaches to establish a positive institutional image while simultaneously enhancing customer trust. Nevertheless, the effectiveness of both strategies at the branch office level remains insufficiently examined empirically. This study aims to analyze the influence of Corporate Branding and Brand Ambassador on Customer Trust at BSI KC Panorama, Bengkulu City, both partially and simultaneously.A causal quantitative method was employed, with data collected through questionnaires distributed to active customers selected via purposive sampling technique. The data were analyzed using multiple linear regression, encompassing the t-test, F-test, and coefficient of determination (R²).The findings demonstrate that Corporate Branding exerts a positive and significant influence on customer trust (t-value = 23.895; sig. = 0.000), as does Brand Ambassador (t-value = 2.543; sig. = 0.012). Simultaneously, both variables were proven to have a significant combined effect on customer trust.It is concluded that Corporate Branding constitutes the most dominant variable in shaping customer trust at BSI KC Panorama, Bengkulu City, indicating that institutional brand image plays a considerably greater role than the ambassador figure in determining customer confidence.